Existence and Uniqueness Theorems For Non- Linear Fractional Differential Equations - Azhaar H. Sallo (College of Education for Pure Sciences, 2006)
In this paper, we study the existence and uniqueness solution for non-linear fractional differential equation which has the form D° [y - Tm_, (y (Xx) = f (xf y (x)) m-l2 With By using Schauder fixed point theorem [4].